IMPLIKASI POLITIK KEBIJAKAN HUKUM PIDANA DALAM UUPLH - David Aprizon Putra (Faculty of Law, University of Muhammadiyah Malang, 2017)
Political Law is one of the discourses that control the existence of law.One of the realm of law that has recently received the spotlight and serious attention. Particularly related to the legal political option is the environment law that increasingly strong day include criminal law enforcement in law enforcement. There are some weak things that then have negative implications, against the enforcement of environmental laws related to the lack of cautious political choice. Since 1982 in Law No. 4 of 1982 on the Principles of Environmental Management which was changed in 1997 into Law No. 27 of 1997 on Environmental Management, the legal politics of criminal law policy has been conducted, that the criminal law policy in the realm of the environment is already a choice of legal politics in the realm of environmental law. Law Number 32 Year 2009 About PPLH as the latest generation, adds Chapter XV of the Criminal Code in its charge of 23 Articles. Law Number 32 Year 2009 contains a much more complete criminal provision than Law Number 23 Year 1997. Although there is still much to be fixed on the provisions of Law Number 32 Year 2009. Base on research shows that there are special procedural laws that regulate formal law enforcement. It is based on the principle of ultimum remedium which means that the implementation of the criminal law must wait until the effectiveness of administrative law is upheld. To minimize obstacles in enforcing environmental laws which are sometimes used by political elites to seek profit, formal laws against environmental crimes should be set up specifically with the Act.